ANALYSIS OF THE SAVING BEHAVIOR TOWARDS MANADO YOUNG GENERATION - Batistuta Manumpil; Maryam Mangantar; Merinda H.C. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
This study aims to identify the Behavior of Manado Young Generation when they do the saving in their formative days. The current study used a qualitative method to determine what elements motivate the Manado City Generation to save. The research study's sample consists of 18 participants of Manado's Young Generation, aged 19 to 26, who have been participating in saving activities for nearly a year. The findings of the research using the interview approach yielded four variables that influence the saving interest of Manado City's Young Generation. Family involvement, peer influence, self-control, and financial literacy all have an impact on their desire to participate in activities. According to the findings, self-control had the greatest evident impact on the Manado City Young Generation's decision to engage in saving activities. These studies might be excellent references for those interested in growing personal savings, as well as a body of knowledge and practical implications.Â